2017
DOI: 10.1136/bmjdrc-2016-000351
|View full text |Cite
|
Sign up to set email alerts
|

Lower glycemic load meals reduce diurnal glycemic oscillations in women with risk factors for gestational diabetes

Abstract: ObjectiveMaternal glycemia plays a key role in fetal growth. We hypothesized that lower glycemic load (GL) meals (lower glycemic index, modestly lower carbohydrate) would substantially reduce day-long glucose variability in women at risk of gestational diabetes mellitus (GDM).Research design and methodsA crossover study of 17 women (mean±SD age 34.8±4 years; gestational weeks 29.3±1.3; body mass index 23.8±4.7 kg/m2) who consumed a low GL or a high GL diet in random order, 1-day each, over 2 consecutive days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 40 publications
(32 reference statements)
0
32
0
Order By: Relevance
“…A study by Rasmussen et al 53 showed that the GV of pregnant women with GDM in the group eating a high-carbon breakfast was significantly higher than that of pregnant women with GDM in the group eating a low-carbon breakfast. Similarly, a small sample study 54 showed that the low-glycemic-load diet significantly reduced the GV index of pregnant women with GDM compared with the high-glycemic-load diet. Dalfra et al 33 found that diet therapy alone can improve GV in pregnant women with GDM.…”
Section: Controlling Gvmentioning
confidence: 89%
See 1 more Smart Citation
“…A study by Rasmussen et al 53 showed that the GV of pregnant women with GDM in the group eating a high-carbon breakfast was significantly higher than that of pregnant women with GDM in the group eating a low-carbon breakfast. Similarly, a small sample study 54 showed that the low-glycemic-load diet significantly reduced the GV index of pregnant women with GDM compared with the high-glycemic-load diet. Dalfra et al 33 found that diet therapy alone can improve GV in pregnant women with GDM.…”
Section: Controlling Gvmentioning
confidence: 89%
“…50,51 Three studies have shown specifically that dietary control can reduce blood glucose fluctuations in pregnant women with GDM. [52][53][54] Studies also have shown that reducing postprandial hyperglycemia can effectively reduce postprandial hyperglycemia peak. Carreiro et al 52 found that receiving dietary consultation can improve the GV of pregnant women with GDM.…”
Section: Controlling Gvmentioning
confidence: 99%
“…In spite of the high inter-and intrapersonal variability of PPGR to the same food, the use of GI data for guiding dietary recommendations has been shown to have significant albeit modest beneficial effects on different health outcomes. Low GI diets have been shown to improve glycemic control [39][40][41], to reduce calculated coronary heart disease (CHD) risk score, to decrease interleukin-6 [42] in people with diabetes, to improve maintenance of weight loss [43], and to considerably reduce diurnal glycemic oscillations in women with risk factors for GDM [44]. Thus, there is good reason to believe that incorporation of GI data into dietary general recommendations will improve a number of health outcomes, but the use of GI/GL data did not considerably increase the accuracy of individual PPGR prediction, which could be used to further improve pregnancy outcomes through personalized nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…However, as glucose is the main energy substrate for fetal growth, maternal dietary carbohydrate intake is an important fetal exposure. Both dietary glycaemic index (GI) and glycaemic load (GL) are markers of dietary carbohydrate quality, and are strong determinants of circulating glucose levels throughout the day during pregnancy [ 18 ]. In turn, blood glucose levels are associated with increased risk of adverse outcomes in the offspring, including being born large-for-gestational age, in a linear dose-dependent manner [ 19 ].…”
Section: Introductionmentioning
confidence: 99%